(3GdYbO GdWgeGSjs - (3GdLHYj, GdYGedj, GdMGQKj, YR GdOjf, MSjf Hf YHO GdUeO Hf eMeO Hf Ydj, J (B984(3g`s ((3YHO GdeLjO cGTa GdZWGAs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd ef GdSeGA eGA WghQG(B... (3ajbhd abjQ QMeI QHg GdZfj GdMSjf Hf YHO GdUeO(B... (3deG hQOJ GdChGeQ GdYGdjI GdZGdjIs
(3BNQgG (B:s
(3ShGA cGf dg eY Pdc JYdb HGdOfjG Ce dG, bd Pdc GdJYdb Ch cKQ(B. (3gPG BNQ eG JjSQ cJGHJg(B...s
(3JHUQI GdYfhGf (B:s
(3aj eYLe GdeDdajf(B: (3GdWQeGSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B615s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B615s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis